Co-crystallization and small molecule crystal form diversity: from pharmaceutical to materials applications. Issue 44 (6th October 2016) - Cherukuvada, Suryanarayan; Kaur, Ramanpreet; Guru Row, Tayur N.
Abstract : The design, manifestation and applications of various co-crystallization products of small molecule supramolecular combinations are presented. Abstract : Co-crystallization is the supramolecular phenomenon of aggregation of two or more different chemical entities in a crystalline lattice through non-covalent interactions. It encompasses the study of the manifestation of multi-component crystalline solids as well as their design. The chemistry community and the literature suggest cocrystals with reference to co-crystallization products and multi-component crystalline solids. Over the last decade cocrystals have become very popular as a potential new/alternate solid form of pharmaceuticals. However, there is no consensus on what exactly a cocrystal means and what it constitutes across academia, industry and regulatory bodies. On the other hand, cocrystals have been endorsed to the extent that the following facts have been obscured: (1) cocrystals are only one of the putative outcomes of co-crystallization, if at all, and (2) their application goes way beyond pharmaceuticals. Solvates, solid solutions, eutectics, salts, ionic liquids, solid dispersions, supramolecular gelators etc. are among the multifarious products of co-crystallization. The manifestation of these supramolecular/non-covalent crystalline adducts is controlled by the inherent nature of the system (the components involved) besides the surroundings (temperature, solvent, pH etc. ); in effect it is a thermodynamic outcome. Each of these adducts, including cocrystals, are unique, exhibit varied physicochemical properties and are amenable to design and therefore have, and potentially find, manifold applications in diverse fields such as organic synthesis & separation, green chemistry, energy storage, solar cells, electronics, luminescent and smart materials, apart from pharmaceuticals. This article highlights the diversity of crystal forms and the utility of small molecule supramolecular combinations.